New Technologies in Swimming Sports - Davide Di Palma; Antonio Ascione (Giornale italiano di educazione alla salute, sport e didattica inclusiva, 2018)
The aim of this research contribution is to bring to the fore the importance that technological progress can play in sports disciplines too, just like what already guaranteed in other sports contexts such as football or formula one. In this regard, we are going to introduce some of the main technologies useful to support technicians, coaches and experts in the field in optimal training planning and in the increase of performance during competitions.